1981
DOI: 10.1126/science.6264607
|View full text |Cite
|
Sign up to set email alerts
|

Δ 9 -Tetrahydrocannabinol Increase Plasma Testosterone Concentrations in Mice

Abstract: Oral administration of delta 9-tetrahydrocannabinol had a biphasic effect on plasma testosterone concentrations in male mice, causing rapid sustained increases at low doses and subsequent decreases at higher doses. In hypophysectomized and intact mice receiving gonadotropins (human chorionic gonadotropin), treatment with delta 9-tetrahydrocannabinol maintained higher plasma testosterone concentrations. Thus, this cannabinoid may interact with gonadotropin and directly influence testicular steroidogenesis in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Other investigators showed that AEA and THC produce similar biphasic responses on Ca 2þ channels in neurons, testosterone secretion in vivo and in vitro, phagocytosis in neutrophils, blastocyst implantation in vivo, trophoblast outgrowth in culture, and behavior of mice (Burstein et al, 1978;Dalterio et al, 1981Dalterio et al, , 1983Mackie et al, 1993;Wang et al, 1999; Munro et al (1993), f Bouaboula et al (1993). NR, not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators showed that AEA and THC produce similar biphasic responses on Ca 2þ channels in neurons, testosterone secretion in vivo and in vitro, phagocytosis in neutrophils, blastocyst implantation in vivo, trophoblast outgrowth in culture, and behavior of mice (Burstein et al, 1978;Dalterio et al, 1981Dalterio et al, , 1983Mackie et al, 1993;Wang et al, 1999; Munro et al (1993), f Bouaboula et al (1993). NR, not reported.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 60 men Halikas et al (1982) reported 68% felt marijuana improved the quality of their orgasm, 39% believed erection duration improved and 90% reported a global sexual improvement. The mechanism may be linked to elevated testosterone levels as shown by Dalterio's mouse model in which there was an acute rise in serum testosterone with THC (Dalterio et al 1981). …”
Section: Marijuanamentioning
confidence: 99%
“…an immediate low ering following treatment with a subsequent marked recovery. In studies with male mice, Dalterio et al [23] have reported that acute oral administration of THC had a biphasic effect on plasma testosterone concentrations, causing rapid sustained increases at low doses (5 mg/kg) and subsequent decreases at high doses (50 mg/kg). This is consistent with our finding of increased testosterone levels at 5.0 mg/kg THC or 15 mg/kg CME, and sug gests that dose, time of administration of cannabinoid, as well as feeding pattern would all contribute to diurnal changes in circulat ing androgens.…”
Section: Discussionmentioning
confidence: 99%